Small for Gestational Age Babies: Morbidity and Immediate Outcome in a Tertiary Care Hospital - A Prospective Study - Dey, Arjun Chandra; Ahmed, Farid Uddin; Mannan, Md Abdul; Saha, Laxmi; Barua, Chowdhury Chiranjib; Mahmood, Chowdhury B (Bangladesh Journal of Child Health, 2010)
Background: Birth weight is the single most important determinant of survival and subsequent growth and development of the newborn. In Bangladesh there is high prevalence of low birth weight (LBW) babies and most of them are small for gestational age. The study was conducted to identify the proportion and category of the small for gestational age babies and determination of the short-term outcome with the aim to the reduction of neonatal mortality and morbidity by problem-wise intervention. Methods: This cross sectional study was conducted in the Neonatal Unit of Chittagong Medical College Hospital, Chittagong between December 2000 and July 2001. Neonates admitted into this unit weighing less than 10th percentile of weight for gestational age were included. On admission the weight was taken and gestational age was calculated using last menstrual period and Ballard score. The infants were monitored daily till discharge or death. Result: A total of 200 SGA babies were included in the study. Among 200 cases 114 were male and 86 were female. All cases were included within 24 hours of age. The anthropometric analysis of the SGA babies showed more than 80% of the SGA babies were normal in length whereas 19.5% fell below 10th percentile of normal. Seventy three percent of SGA babies were asymmetrically (disproportionate) and 27% of babies were symmetrically (proportionate) growth retarded. The main problems associated with the SGA babies were perinatal asphyxia (65.5%), sepsis (54%), jaundice (42.0%), hypothermia (31%), apnea (29%), hypoglycemia (25%), and bleeding manifestations (9%). Asymmetrical SGA babies were at higher risk of infection and jaundice. Present study revealed the mortality of SGA babies were 17% and mortality was significantly higher among the neonates from low socio-economic status and having very low birth weight, hypothermia, apnea, sepsis, bleeding manifestations, and polycythemia. Conclusion: Findings in this study could be important in identifying the areas requiring attention to improve perinatal care in order to prevent SGA babies and also to manage the problems associated with them. DOI: 10.3329/bjch.v31i1.6066 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 1-7